Implementasi Kebijakan Pembatasan Penggunaan Kemasan Plastik Sekali Pakai Dan Styrofoam Di Kota Palu - Fahrial, Abdul Azis; Djaelangkara, Rizali; Tawil, Yulizar Pramudika (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to determine the implementation of restrictions on the use of disposable plastic packaging and Styrofoam in the city of Palu. The basis of research used is field research and descriptive qualitative research type. The informants in this study were the Environmental Agency of Palu City, business actors, modern stores, plastic manufacturers and the people of Palu City. Data collection techniques through informants accompanied by observation, interviews, and documentation and using the basis of Van Metter and Van Horn Implementation theory which consists of 6 (six) variables, namely, Policy Standards and Infrastructure, Resources, Communication Between Implementing Agencies, Characteristics of Implementing Agencies, Social, Economic, and Political Environment, Implementing Attitudes. Based on the results of the study, it shows that the Implementation of the Policy on Limiting the Use of Disposable Plastic Packaging and Styrofoam in Palu City has not run optimally on several indicators, namely Policy Standards and Objectives, Resources, Communication Between Implementing Agencies, Social, Economic and Political Environment and Implementing Attitudes. Because of the lack of massive socialization and the lack of understanding and awareness of policy targets who do not know the impact of environmental damage, seeing in terms of operations has not been handled properly, in Resources there are still many shortcomings from human resources, in terms of enforcement and handling and lack of infrastructure in transporting waste, then in Communication Between Implementing Agencies has not conducted massive socialization starting from the implementers to the Policy targets, in the Characteristics between Implementing Agencies all involved in the implementation are in accordance with their respective fields, as well as in the Social, Economic and Political environment has supported the Implementation of this Policy even though in terms of the Economy it has not been said to be well implemented, and the Attitude aspect of Implementers requires assertiveness in the Implementation of these policies to avoid problems that will occur in policy implementation. All forms of this problem need improvement so that in the future it runs well and effectively.